ANALISIS TINGKAT PENDAPATAN DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gui, Shally; Effendy, Syahril (LPPM Universitas Putera Batam, 2021)
This study aims to test and analyze the effect of the level of income and operating costs on net income in companies listed on the Indonesia Stoct Exchange in the period 2015 to 2019. The population used in this studt were 33 companies and the sample in this study were 13 companies that were taken using non-probability sampling techniques, namely income partially has a significant effect on net income, namely tcount of 2,835> 2.026 ttable, but operating costs do significantly influence net income, namely tcount of 2,527 > ttable 2,026. Based on the results of the F test research, it is found the the level of income and operational costs simultaneuously have a significant effect on net income by showing the value of Fcount 13,315 >3.25 Ftable. In this study, the coefficient of determination shows that net income can be explained by the level of income and operating costs of 68.6%, while the remaining 31.4% of net income is influenced by other factors.